Hipo-utopia, das utopias urbanas ao sul: a cidade contemporânea no cinema brasileiro de ficção científica - Margotto, Mário Victor Marques (2021)
Through an exploratory research, seeks a first approach to an object little studied when taken as a group – which inhabits a “rarefied atmosphere” (SUPPIA, 2007): the cities represented in Brazilian science fiction cinema. In addition to a bibliographic review and a theoretical reflection, utilizes film analysis in order to explore the cities represented in three contemporary works: Cold Tropics (Recife Frio) (2009), White Out, Black In (Branco Sai, Preto Fica) (2014) and Chico (2016). First, starts with a discussion regarding “urban utopias”, as proposed by Caúla (2019), bringing and expanding the concept of “hipo-utopia” (FERREIRA, 2015) to contextualize, categorize and characterize both the group of science fiction films produced in the Global South, as well as the urban utopias produced by Brazilian science fiction cinema. Furthermore, comments on the modernization and urbanization process in the Brazilian historical context, highlighting its condition permeated by inequalities, discrepancies and contradictions (MARICATO, 2000, 2015), in order to reinforce the compatibility of the concept of “hipo-utopia”, as well as to illustrate and contextualize the urban reality through which this category of film aims to explore through its speculations. Concerning the film analysis, two inputs are used to explore these representations: on the one hand, the elements of science fiction narrative, the "novum" and the "cognitive estrangement" (SUVIN, 1979), and, on the other hand, the interpretation of scenarios and spaces through the possibilities of the cinematographic language and the aesthetics developed by each work. Understanding that this cinema produces its other-places from the filmed city (COMOLLI, 1997) – through cuts and decisions that are characteristic of the seventh art –, the urban space itself turns out a protagonist that, on the one hand, singles out the city, and, on the other, highlights its elements. In this regard, besides the films address the social disparities of a peripheral region regarding modernization (FERREIRA, 2012; GINWAY and BROWN, 2014; PAZ, 2008), these “science fiction cities” (MUSSET, 2007) are also enhanced as a place of estrangement, which these movies explore. A first step was taken to understand the studied object, however, there are relevant issues that, given its complexity, were not developed in this research, requiring further studies.